A reassessment of the extinction risk of the Critically Endangered Oxapampa poison frog Ameerega planipaleae (Dendrobatidae). Issue 3 (13th September 2018) - Angulo, Ariadne; von May, Rudolf; Icochea, Javier
Abstract: Assessments of extinction risk are required to inform conservation action, but the usefulness of assessments is undermined if they are not current. Ameerega planipaleae, a poison frog endemic to the cloud forests of central Peru, was last assessed in 2004. We therefore sought to provide updated data to inform the reassessment of this species. Based on our findings, we recommend that this frog remain categorized as Critically Endangered, but under modified criteria, and that conservation actions are taken to reduce the pressures of local threats, especially the overuse of agrochemicals.